2014
DOI: 10.21240/mpaed/24/2014.09.04.x
|View full text |Cite
|
Sign up to set email alerts
|

Ein kulturökologischer Rahmen für Mobilität und Lernen

Abstract: Mobile devices and services have achieved a level of critical mass and importance that requires us to take them seriously as new cultural resources. Mobile cultural resources emerge within what we call a ‹mobile complex›, which consists of the inter­play of structures, agency and cultural practices. These new cultural resources also can be considered to be valid learning resources which are ‹complex› because the components of the triangular structuration model, that governs them, interact with each other in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Mobile-assisted language learning is now a well-established field and one which has had an enormous impact on L2 teaching and learning (Pachler et al, 2010). The availability and functionality of mobile devices is leading to an increase in informal, self-directed, out-of-class mobile learning, where smartphones give learners the opportunity to create ‘impromptu sites of learning’ (Bachmair and Pachler, 2014; Kukulska-Hulme et al, 2017). A recent meta-analysis demonstrated that mobile learning was more effective in informal instructional settings than in formal settings (Sung et al, 2016).…”
Section: Future Directionsmentioning
confidence: 99%
“…Mobile-assisted language learning is now a well-established field and one which has had an enormous impact on L2 teaching and learning (Pachler et al, 2010). The availability and functionality of mobile devices is leading to an increase in informal, self-directed, out-of-class mobile learning, where smartphones give learners the opportunity to create ‘impromptu sites of learning’ (Bachmair and Pachler, 2014; Kukulska-Hulme et al, 2017). A recent meta-analysis demonstrated that mobile learning was more effective in informal instructional settings than in formal settings (Sung et al, 2016).…”
Section: Future Directionsmentioning
confidence: 99%
“…Mobile learning has been widely acclaimed for its revolutionary and liberating redefinition of learning in which, with the assistance of mobile devices, learners are given increased mobility to create “impromptu sites of learning” and personalized learning ecologies (Bachmair & Pachler, 2014; Kukulska-Hulme, Gaved, Jones, Norris & Peasgood, 2017; Kukulska-Hulme & Sharples, 2016; Wong, Milrad & Specht, 2015). The conceptualized mobile learning culture rests essentially on learner agency and ability to utilize the enhanced mobility to construct learning experiences across time and space (Burston, 2014a; Kukulska-Hulme, 2012; Underwood, Luckin & Winters, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Central to this argument is the fact that educational institutions no longer have control over this process-for a change, students do. The contexts where learning and teaching occurred changed overnight during the emergency remote online teaching phase-off-campus and into the informal spaces students dwell inincluding the cultural, social, digital and temporal spaces (Bachmair & Pachler, 2014). This change significantly impacts the type of content that is traditionally created by the teacher for the students, the learning tasks and activities, assessment and learning scaffolds.…”
Section: Literature Reviewmentioning
confidence: 99%